1996
DOI: 10.1073/pnas.93.23.12932
|View full text |Cite
|
Sign up to set email alerts
|

NMR of laser-polarized xenon in human blood

Abstract: By means of optical pumping with laser light it is possible to enhance the nuclear spin polarization of gaseous xenon by four to five orders of magnitude. The enhanced polarization has allowed advances in nuclear magnetic resonance (NMR) spectroscopy and magnetic resonance imaging (MRI), including polarization transfer to molecules and imaging of lungs and other void spaces. A critical issue for such applications is the delivery of xenon to the sample while maintaining the polarization. Described herein is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
139
1
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(146 citation statements)
references
References 24 publications
5
139
1
1
Order By: Relevance
“…These earlier studies suggested the following peak assignments: 187.2 ppm, muscle 19, 20, 21; 192.7 ppm, white matter (and soft‐tissue in this study) 18, 19, 20, 21; 195.6 ppm, gray matter 18, 19, 20, 21; 199.6 ppm, aqueous solution (cerebrospinal fluid, plasma, and interstitial fluid in this study) 10, 11, 24, 25, 26 and fat/lipid tissue outside the brain 19, 20; and 217.2 ppm, red blood cells 4, 10, 24, 26.…”
Section: Discussionsupporting
confidence: 65%
“…These earlier studies suggested the following peak assignments: 187.2 ppm, muscle 19, 20, 21; 192.7 ppm, white matter (and soft‐tissue in this study) 18, 19, 20, 21; 195.6 ppm, gray matter 18, 19, 20, 21; 199.6 ppm, aqueous solution (cerebrospinal fluid, plasma, and interstitial fluid in this study) 10, 11, 24, 25, 26 and fat/lipid tissue outside the brain 19, 20; and 217.2 ppm, red blood cells 4, 10, 24, 26.…”
Section: Discussionsupporting
confidence: 65%
“…129 Xe displays an NMR spectrum with chemical shifts in resonance frequency that characterize its microscopic/molecular environment [14,15]. It offers longitudinal magnetization that survives several seconds to several tens of seconds in vivo [16,17]. The time and spatial dependence of its distribution in the body can reveal functional attributes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The Xe atom has a large electric dipole polarizability; cavities within proteins are about the correct size to hold one or more Xe atoms, and the unfavorable entropic term related to the need to orient the ligand in the binding site is absent for Xe atom. The affinity of Xe for hydrophobic cavities in the interiors of macromolecules (5)(6)(7)(8)(9)(10) coupled with the development of techniques for hyperpolarization of Xe nuclear spins have inspired an array of NMR studies of Xe in proteins (11), cells, (12,13), and tissues (14)(15)(16). For example, hyperpolarized (HP) 129 Xe has been developed as a tool for the characterization of protein cavities which bind Xe, by using its nuclear spin polarization to enhance the signals of the protons in the cavity (10,17), by using the Xe chemical shift itself as a reporter of cavity structure in both solution and the solid state (11), and in applications to biomolecular assays (18,19).…”
mentioning
confidence: 99%